The breast cancer genetic testing experience: probing the potential utility of an online decision aid in risk perception and decision making - Anna Vaynrub; Brian Salazar; Yilin Eileen Feng; Harry West; Alissa Michel; Subiksha Umakanth; Katherine D. Crew; Rita Kukafka (BMC Cancer)
Abstract Background Despite the association of pathogenic variants (PVs) in cancer predisposition genes with significantly increased risk of breast cancer (BC), uptake of genetic testing (GT) remains low, especially among ethnic minorities. Our prior study identified that a patient decision aid, RealRisks, improved patient-reported outcomes (including worry and perceived risk) relative to standard educational materials. This study examined patients’ GT experience and its influence on subsequent actions. We also sought to identify areas for improvement in RealRisks that would expand its focus from improved GT decision-making to understanding results. Methods Women enrolled in the parent randomized controlled trial were recruited and interviewed. Demographic data was collected from surveys in the parent study. Interviews were conducted, transcribed, and coded to identify recurring themes. Descriptive statistics were generated to compare the interviewed subgroup to the original study cohort of 187 women. Results Of the 22 women interviewed, 11 (50%) had positive GT results, 2 (9.1%) with a BRCA1/2 PV, and 9 (40.9%) with variants of uncertain significance (VUS). Median age was 40.5 years and 15 (71.4%) identified as non-Hispanic. Twenty (90.9%) reported a family history of BC, and 2 (9.1%) reported a family history of BRCA1/2 PV. The emerging themes included a preference for structured communication of GT results and the need for more actionable knowledge to mitigate BC risk, especially among patients with VUS or negative results. Few patients reported lifestyle changes following the return of their results, although they did understand that their behaviors can impact their BC risk. Conclusions Patients preferred a structured explanation of their GT results to facilitate a more personal testing experience. While most did not change lifestyle behaviors in response to their GT results, there was a consistent call for further guidance following the initial discussion of GT results. Empowering patients, especially those with negative or VUS results, with the context to internalize the implications of their results and form accurate risk perception represents a powerful opportunity to optimize subsequent risk management strategies. Informed by this study, future work will expand RealRisks to include the return of results and decision support to navigate concrete next steps.